2019
DOI: 10.1161/jaha.119.012558
|View full text |Cite
|
Sign up to set email alerts
|

Use of Diffusion‐Weighted Imaging‐Alberta Stroke Program Early Computed Tomography Score (DWI‐ASPECTS) and Ischemic Core Volume to Determine the Malignant Profile in Acute Stroke

Abstract: BackgroundMalignant profiles were identified by imaging profiles and unfavorable outcomes that have poor response to reperfusion therapy. Many trials have used this profile in their inclusion criteria including large‐vessel occlusion acute ischemic stroke trials. We aimed to redefine the cutoff values for malignant profile in acute ischemic stroke patients with large‐vessel occlusion regardless of reperfusion therapy.Methods and ResultsConsecutive acute ischemic stroke patients with anterior large‐vessel occlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 22 publications
0
35
1
Order By: Relevance
“…Thus, some of these patients might not have imaging predictors of MMI. Although a DWI-ASPECTS ≤ 6 has previously been shown to be associated with a DWI lesion volume >100 mL [11], a recent study demonstrated a significant divergence between DWI-ASPECTS and DWI lesion volume assessment when DWI-ASPECTS is <7 [16]. Indeed, in our study, almost half of the patients with a DWI-ASPECTS ≤ 6 had a DWI lesion volume <82 mL.…”
Section: Discussioncontrasting
confidence: 70%
“…Thus, some of these patients might not have imaging predictors of MMI. Although a DWI-ASPECTS ≤ 6 has previously been shown to be associated with a DWI lesion volume >100 mL [11], a recent study demonstrated a significant divergence between DWI-ASPECTS and DWI lesion volume assessment when DWI-ASPECTS is <7 [16]. Indeed, in our study, almost half of the patients with a DWI-ASPECTS ≤ 6 had a DWI lesion volume <82 mL.…”
Section: Discussioncontrasting
confidence: 70%
“…Diffusion-weighted imaging (DWI) has a higher diagnostic value for ischemic stroke, which provides therapeutic considerations for ischemic stroke intervention [3,4]. Recent studies have shown that a pretreatment lesion volume >70 mL is highly predictive of a poor clinical outcome, while 100 mL lesion volume has also been reported to be predictive of symptomatic hemorrhagic transformation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…DWI-ASPECTS and the core volume show a weak correlation when DWI-ASPECTS is under 6, which is approximately >33 ml in the adult ischemic stroke population [ 6 ]. Blurry DWI lesions are sometimes biased by ASPECT scoring, and on the other hand, are underestimated by automated software.…”
Section: Discussionmentioning
confidence: 99%